Conflict Between Coastal Tourism Development and Sustainability: case of Mostaganem, Western Algeria - Taibi, Nasr-Eddine (European Journal of Sustainable Development, 2016)
Dependency on oil and gas incomes has urged Algeria to support tourism development as a means of creating other sources of wealth. However, this is not done without environmental damages. Indeed, the insufficient number of host accommodations at the coastal areas has led to chaotic construction projects. Mostaganem is an example. It attracts recently 11 million tourists yearly, although it lacks in host accommodation. To overcome this issue, new tourist infrastructures close to the shoreline and among the coastal dunes have been programed regardless of the Littoral law that protects the coastal strip (300 m). Moreover, the wastewater issue is neither discussed nor solved, in spite of a lack of wastewater treatment plants in this area. This work is based on data collected from the Algerian Government, and the Ministry of Land-use Planning, Tourism, and Handicraft. Shore urbanization endangers the sustainability of the beaches as a socioeconomic resource. Seaside tourism could be developed without any beach urbanization by constructing in the nearby coastal rural municipalities. Tourists would enjoy the beach during the day and would return to their accommodation in the rural municipality. This would benefit economically both the local population and the environment. Key words: Coastal tourism, Construction, Littoral law 02/2002, Sustainability, Socioeconomic, Mostaganem, Algeria.